The Entitlement of a State to Jurisdictional Immunity under International Law - Alexandr N. Vylegzhanin; Nadezhda A. Churilina (Московский журнал международного права, 2015)
The article shows that the state immunity from the authority of another state, including the judicial, with various theoretical estimates, should be considered under the designated regulatory format as a principle of international law reflected in its main sources, primarily in the international custom. In an ambiguous understanding of this principle’s content in national law and state practice the results of the work of the International Law Commission (draft articles on jurisdictional immunities of States and their property, 1991) and, especially, the elaboration of the United Nations Convention on jurisdictional immunities of States and their property, 2004, have been undoubtedly positive. They have already been estimated as the initial regulatory balance between the guarantees of state immunity and the reasonability of protecting the economic actors’ competitiveness as a fundamental value for the world economic development Taking this into consideration the interpretation of state immunity rules by the International Court of Justice as the principal judicial organ of the United Nations has been investigated.